2019
DOI: 10.1002/ett.3800
|View full text |Cite
|
Sign up to set email alerts
|

Daylight integrated indoor VLC architecture: An energy‐efficient solution

Abstract: In an indoor space, visible light communication (VLC) can form a promising enhancement of future illumination infrastructures with communication functionalities. This illumination infrastructure consumes 20% of the total energy consumption in the world. In this perspective, daylight integration with indoor VLC system is a promising area of research to conserve a considerable amount of energy. This paper deals with the design and practical realization of an energy‐efficient indoor VLC system through daylight in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, light interference, this is due to the overlapping with the other neighboring light sources and sunlight 12 . However, different techniques are proposed in the literature for reduction of such interference 73‐76 . For example, authors of Reference 73 suggested choosing a suitable transmission band, which experiences relatively less interference by other light sources, to tackle the effect of this type of interference.…”
Section: Inside Train Communicationmentioning
confidence: 99%
“…Furthermore, light interference, this is due to the overlapping with the other neighboring light sources and sunlight 12 . However, different techniques are proposed in the literature for reduction of such interference 73‐76 . For example, authors of Reference 73 suggested choosing a suitable transmission band, which experiences relatively less interference by other light sources, to tackle the effect of this type of interference.…”
Section: Inside Train Communicationmentioning
confidence: 99%
“…Even in high‐speed railway VLC can find its application 11 to facilitate the improved connectivity. As the lighting fixtures are everywhere and recently replaced by the white light‐emitting diode (WLED) 12,13 it can be used as a transmitter for simultaneous data transmission. This upheaval in the lighting paradigm creates an opportunity for VLC to be commercially viable in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…But the scheme requires more computing resources and overlooks the camera's capturing angles. Comparing with visible light channel communication schemes, [9][10][11] the invisible screen-camera short-range communication method is not required extra hardware while ensuring imperceptible for human eyes. There is an invisible screen-camera communication schemes called HA-QL in IEEE 802.15.7-2018 standards.…”
Section: Introductionmentioning
confidence: 99%